2021
DOI: 10.3390/biom11101402
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Trained Immunity

Abstract: The characteristics of innate immunity have recently been investigated in depth in several research articles, and original findings suggest that innate immunity also has a memory capacity, which has been named “trained immunity”. This notion has revolutionized our knowledge of the innate immune response. Thus, stimulation of trained immunity represents a therapeutic alternative that is worth exploring. In this context, probiotics, live microorganisms which when administered in adequate amounts confer a health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 180 publications
0
13
0
Order By: Relevance
“… 52 Further, microbial metabolites, including those produced by probiotics, have the potential to travel to the bone marrow where they epigenetically imprint hematopoietic progenitors. 53 , 54 Therefore, selective modulation of the intestinal microbiota could have long-term benefits to the host and it is of great importance to determine which probiotics or probiotic compounds that are capable of imprinting memory responses in innate cells. This could be beneficial for future therapeutic interventions where, for instance, excessive inflammation is necessary to be regulated.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Further, microbial metabolites, including those produced by probiotics, have the potential to travel to the bone marrow where they epigenetically imprint hematopoietic progenitors. 53 , 54 Therefore, selective modulation of the intestinal microbiota could have long-term benefits to the host and it is of great importance to determine which probiotics or probiotic compounds that are capable of imprinting memory responses in innate cells. This could be beneficial for future therapeutic interventions where, for instance, excessive inflammation is necessary to be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that anti-TLR2 antibody blocked LAB-induced IFN-γ and TNF-α secretion but had no inhibitory effect on IL-12. Thus, the immune responses of HY8002 and HY7717 may be associated with PRRs such as other TLRs or NOD-like receptors (NLRs) [ 52 ]. TLR2 is a major receptor of both HY8002 and HY7717 and promotes immune activity in splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, by fermenting dietary fibers, probiotics can produce SCFAs (short-chain fatty acids), such as butyrate, propionate, and acetate, with protective properties against intestinal pathogens [ 44 ]. Moreover, probiotics have been associated to decreased secretion of inflammatory cytokines such as tumor necrosis factor-α, interferon-γ, and interleukin-1, and increased production of the anti-inflammatory cytokines such as interferon-α and interleukin-10 [ 45 , 46 , 47 ]. Some species displayed the capacity to stimulate immunoglobulin A secretion in Peyer patches [ 48 ].…”
Section: Probiotics and Their Mechanisms Of Actionsmentioning
confidence: 99%